Peran Kepala Sekolah Sebagai Supervisor Pendidikan Dalam Meningkatkan Kompetensi Profesional Guru di SMP Quran Darul Fattah Bandar Lampung - Syahyudi, Arman; Pahrudin, Agus; Hadiati, Eti; Ayu, Sovia Mas; Junaidah, Junaidah (El-Idare, 2023)
The principal as a supervisor has the responsibility to improve the teacher's ability to manage the learning process and has an important role in the progress and development of the school. This research is a qualitative research. The data sources used are primary data sources and secondary data sources. The collection techniques used in this study used observation, interviews, and documentation. The data analysis technique used in this study was data collection, data condensation, data presentation and conclusion. Test the validity of the data by using data triangulation. The results of this study indicate that the principal as a supervisor has provided guidance to teachers in carrying out the learning process at school. The principal has supervised the teacher properly and directly in the classroom during the learning process. Principals have developed teacher abilities by conducting training or attending seminars in supporting teacher abilities. The principal has demanded that teachers use strategies in providing material at school so that students become more enthusiastic about learning. The principal as a supervisor has carried out his duties well at school so that the teachers at the school can improve the quality of providing material and become more professional at work.